Play Active physical activity policy intervention and implementation support in early childhood education and care: results from a pragmatic cluster randomised trial - Emma K. Adams; Andrea Nathan; Stewart G. Trost; Jasper Schipperijn; Trevor Shilton; Georgina Trapp; Clover Maitland; Ashleigh Thornton; Matthew Mclaughlin; Phoebe George; Elizabeth Wenden; Hayley Christian (BMC, 2023)
Abstract Background Policy interventions to increase physical activity in early childhood education and care (ECEC) services are effective in increasing physical activity among young children. However, a large proportion of ECEC services do not have nor implement a physical activity policy. Play Active is an evidence-informed physical activity policy intervention with implementation support strategies to enable ECEC services to successfully implement their policy. This study examined the effectiveness, implementation, and process outcomes of Play Active. Methods A pragmatic cluster randomised trial in 81 ECEC services in Perth, Western Australia was conducted in 2021. Services implemented their physical activity policy over a minimum of three months. The effectiveness outcomes were changes in educator practices related to daily time provided for total physical activity and energetic play. Implementation outcomes included changes in director- and educator-reported uptake of policy practices and director-reported uptake of high impact and low effort policy practices. Process evaluation outcomes included awareness, fidelity, reach, and acceptability of the intervention and implementation strategies. Analysis involved descriptive statistics and generalised linear mixed effects models. Results There was a significant increase in the uptake of director-reported policy practices (p = 0.034), but no change in the uptake of the subset of high impact and low effort policy practices. Intervention group educators reported high awareness of the Play Active policy recommendations (90%). Play Active acceptability was high among educators (83%) and directors (78%). Fidelity and reach were high for most implementation support strategies (> 75%). There were no significant changes in the amount of physical activity or energetic play educators provided to children or in the proportion of educators providing the policy recommended ≥ 180 min of physical activity/day or ≥ 30 min of energetic play/day for intervention compared to wait-listed comparison services. Conclusions Play Active resulted in significantly higher uptake of physical activity practices. However, there was no change in the amount of physical activity provided to children, which may be explained by the relatively short policy implementation period. Importantly, Play Active had high awareness, fidelity, reach, and acceptability. Future research should investigate the effectiveness of Play Active over longer implementation periods and its scalability potential. Trial registration Australian New Zealand Clinical Trials Registry (reference number 12620001206910, registered 13/11/2020, https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=378304&isReview=true ).